2019
DOI: 10.1186/s13756-019-0532-4
|View full text |Cite
|
Sign up to set email alerts
|

A national survey on the implementation of key infection prevention and control structures in German hospitals: results from 736 hospitals conducting the WHO Infection Prevention and Control Assessment Framework (IPCAF)

Abstract: Background Healthcare-associated infections (HAI) pose a burden on healthcare providers worldwide. To prevent HAI and strengthen infection prevention and control (IPC) structures, the WHO has developed a variety of tools and guidelines. Recently, the WHO released the Infection Prevention and Control Assessment Framework (IPCAF), a questionnaire-like tool designed for assessing IPC structures at the facility level. The IPCAF reflects the eight WHO core components of IPC. Data on the implementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 26 publications
3
69
2
3
Order By: Relevance
“…However, given the rather low scores achieved by Austrian hospitals for CC5 (Multimodal Strategies for Implementation of IPC Interventions), it appears that awareness for and implementation of multimodal strategies are not yet fully accomplished. A similar deficit was illustrated in an analysis of the German IPCAF data [8]. A conclusion, which could be derived from these data, is that any efforts to strengthen IPC in high-income countries, should place an emphasis on multimodal strategies.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…However, given the rather low scores achieved by Austrian hospitals for CC5 (Multimodal Strategies for Implementation of IPC Interventions), it appears that awareness for and implementation of multimodal strategies are not yet fully accomplished. A similar deficit was illustrated in an analysis of the German IPCAF data [8]. A conclusion, which could be derived from these data, is that any efforts to strengthen IPC in high-income countries, should place an emphasis on multimodal strategies.…”
Section: Discussionsupporting
confidence: 58%
“…Participation was on a voluntary basis. The specifics of survey organization were described in more detail in a previous publication [8]. To comply with data protection regulations, no linkage of survey data with other structural and process parameters, or data on HAI was undertaken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a study conducted in Nepal, a developing Asian country, reported that only 27% of the participants (doctors and nurses) had received infection prevention and control training [19]. This is in stark contrast to results of a study conducted in a developed country where high proportion (> 99%) of the healthcare facilities imparted educational courses about infection prevention and control [15]. Health education and training is crucial to impart knowledge regarding IPC and thereby improve IPC implementation.…”
Section: Discussionmentioning
confidence: 88%
“…Our results are in contrast to developed countries like Germany, where a nationwide study was conducted using the IPCAF tool in 736 hospitals. Only three facilities fell into the category of basic (score between 200 and 400) and 622 facilities were in the advanced group (score between 600 and 800) [15]. The classification of inadequate was not assigned to any healthcare facility.…”
Section: Discussionmentioning
confidence: 99%